1989
DOI: 10.1128/iai.57.12.3936-3939.1989
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant tumor necrosis factor alpha protects susceptible A/J mice against lethal Plasmodium chabaudi AS infection

Abstract: The effect of intravenous treatment with human recombinant tumor necrosis factor alpha (rTNF-oa) on infection of susceptible A/J and resistant C57BL/6 mice with Plasmodium chabaudi AS was examined. Treatment of A/J mice with 103 or 105 U of rTNF-a on days 0, 3, 5, 7, and 9 after intraperitoneal infection with 106 parasitized erythrocytes resulted in 80% survival and a significant decrease in the peak parasitemia level.Treatment of susceptible A/J hosts with 105 but not 103 U of rTNF-a resulted in increased sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…We also show, however, that blocking TNF-a either alone, or in combination with IFN-g, enhances parasitemia. Although the antiparasitic effect of TNF-a has been previously reported , Stevenson & Ghadirian 1989, the present study identifies parasite-specific CD4 þ T cell activation as being critical to the production of TNF-a. We are not sure of the mechanism of action of CD4 þ T celldependent TNF-a.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We also show, however, that blocking TNF-a either alone, or in combination with IFN-g, enhances parasitemia. Although the antiparasitic effect of TNF-a has been previously reported , Stevenson & Ghadirian 1989, the present study identifies parasite-specific CD4 þ T cell activation as being critical to the production of TNF-a. We are not sure of the mechanism of action of CD4 þ T celldependent TNF-a.…”
Section: Discussioncontrasting
confidence: 58%
“…Evidence from human and animal models suggests that CD4 þ T cells play an important role in immunity (Brown et al 1986, Cavacini et al 1986, Brake et al 1988, Suss et al 1988, Troye-Blomberg & Perlmann 1988, Kumar et al 1989, Quakyi et al 1994, Amante & Good 1997. Furthermore, interferon (IFN)-g and tumour necrosis factor (TNF)-a are known to be able to inhibit parasite growth in vivo (Taverne et al 1987, Shear et al 1989, Stevenson & Ghadirian 1989), suggesting that parasite-activated T cells might work via a cytokine cascade, probably in the spleen (Kumar et al 1989, Favila-Castillo et al 1996. Although the final effector molecules that mediate parasite death are not known, reactive nitrogen intermediates (Rockett et al 1991, Taylor-Robinson et al 1993, Jacobs et al 1995, and oxygen radicals (Clark & Hunt 1983, Wozencraft et al 1984 have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Many years ago we observed that multiplication of P. berghei, for instance, was not controlled by treating mice with tumour necrosis serum containing TNF, whereas that of the nonlethal P. yoelii was [38], and that recombinant human TNF delayed the multiplication of a lethal P. yoelii [39]. On the other hand, as others have found, the parasitaemia of P. chabaudi is not affected by TNF [40].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, treatment of resistant B6 mice with an anti-TNF-␣ polyclonal antibody or aminoguanidine, an iNOS inhibitor, resulted in increased mortality, indicating that both TNF-␣ and NO have a protective role in the early phase of blood stage P. chabaudi AS malaria (18,19). In addition, treatment of susceptible A mice with human recombinant TNF-␣ protected these mice from an otherwise lethal infection (30).…”
mentioning
confidence: 99%